COMPARISON OF ALVARADO SCORE AND RIPASA SCORE IN DIAGNOSIS OF ACUTE APPENDICITIS AT HJ. BUNDA HALIMAH HOSPITAL BATAM - Muhammad Azmi Fanany; Fachrul Jamal; Malahayati Rusli Bintang; Raju Sabran (Universitas Batam, 2025)
ABSTRACT Background: Acute appendicitis is the most common abdominal surgical emergency, requiring rapid and accurate diagnosis to prevent serious complications. The Alvarado and RIPASA scores are widely used diagnostic tools, but they differ in characteristics and performance, particularly in Southeast Asian populations. This study sought to compare the Alvarado and RIPASA scores for diagnosing acute appendicitis at Hj. Bunda Halimah Hospital, Batam. Methods: This retrospective cross‑sectional analytic study included 125 patients with suspected acute appendicitis who underwent surgery at Hj. Bunda Halimah Hospital between 1 January 2022 and 31 December 2024. Histopathology served as the gold standard. Diagnostic metrics were calculated for an Alvarado cut‑off ≥ 7 and a RIPASA cut‑off ≥ 8 Results: The Alvarado score showed a sensitivity of 87.7%, specificity of 63.6%, PPV of 96.1%, NPV of 33.3%, and accuracy of 85.6% with an AUC of 0.797. The RIPASA score has a higher sensitivity of 91.2% but lower specificity of 54.5%, PPV of 95.4%, NPV of 37.5%, accuracy of 88%, and an AUC of 0.847. The ROC comparison shows that the AUC value of RIPASA reflects better discriminatory ability in establishing the diagnosis of acute appendicitis. Conclusion: The RIPASA score has been shown to be more sensitive and provide better discriminatory performance. Although the Alvarado score is more specific, the higher sensitivity and accuracy of RIPASA make it a superior alternative in the initial evaluation of appendicitis. Keyword : Acute appendicitis, Alvarado score, RIPASA score